PENGARUH INTANGIBLE ASSET, FINANCIAL FLEXIBILITY, GREEN INNOVATION, DAN HUMAN CAPITAL TERHADAP SUSTAINABLE GROWTH PERUSAHAAN HIGH PROFILE YANG TERDAFTAR DI BEI - Luluk Citrahartani; R. Rosiyana Dewi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
This research aims to examine the influence of intangible assets, financial flexibility, green innovation, and human capital on sustainable growth of companies, with firm size and return on assets (ROA) as control variables. The study uses a sample of 136 high-profile companies from the period of 2018 to 2021, with total of 544 observations. Through descriptive statistical tests, panel data model testing, hypothesis testing, and multiple linear regression analysis, the findings of this study indicate that intangible assets and financial flexibility have a positive effect on sustainable growth. However, green innovation and human capital have a negative impact on sustainable growth of companies. These results suggest that valuable intangible assets and good financial flexibility contribute to enhancing sustainable growth, whereas high levels of green innovation and human capital may not always have a positive impact on sustainable growth. Further research is recommended to understand the reasons why green innovation and human capital have a negative influence on the sustainable growth of companies.